O livro ilustrado: entre a palavra e a imagem - Silva, Eli Neuza Soares da (2015)
The illustrated book: amid the word and image Literature is art, and children’s literature is the artistic expression whose essence is based on verbal and visual dialogue. The children's illustrated book can be characterized by detail, the set of images and the readings of illustration, which, beyond their interrelations with the text, has configurational and structural qualities perfectly explainable and analyzable. Throughout its historical evolution, experienced great innovations, culminating in the current format, on which, gradually, has been conquering a determinant space, building its own history. In the constitutive aspects can guide the child paths for visual reading, and awareness of the look. Whereas the images of child's illustrated book produce in little reader the visual memory, they always have to dialogue harmonically with the word. After all, what is expected from a picture in illustrated book is that it wakes up the look, awake the memories of other images and stimulates in the child reader a new discovery look. To highlight these aspects, this research took as the main subject the relationship between illustration and literary text in children's literature. The sequence of this work had as a priority the analysis of the main influences that composed the language of illustrating children's book art. The main result of the collected data will serve as a support to the realization of a children's interactive book illustrated with origami, that will fulfill three purposes, which are: to serve as a record for future research and studies, to stimulate the pleasure of reading and creative production in child reader as well as to provide the professionals of the analyzed field with a broader and playful vision of illustration in children's literature. Key-words: illustrated book, childish literature, origami